The Role of Omega-3 on the IL-6 Levels, Malondialdehyde, and Clinical Improvement in Adults with Community-Acquired Pneumonia - Astarini, Dewi; Aphridasari, Jatu; Setijadi, Ana Rima (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Acute lung parenchymal infection, known as pneumonia, can be carried on by multiple microorganisms, including bacteria, viruses, fungi, and parasites. Globally, community-acquired pneumonia is a major factor of morbidity, mortality, and health issues. Malondialdehyde (MDA) is a marker of oxidative stress in pneumonia patients, and interleukin 6 (IL-6) is a marker of inflammatory process. Effect of Omega-3 as an immunomodulator, anti-inflammatory, and antioxidant may be implemented as adjunctive therapy in patient with community-acquired pneumonia.Methods: Clinical trial research with a true experimental method and pretest-posttest design. The study involved 30 community-acquired pneumonia patients who were admitted at Moewardi Hospital in Surakarta and Dr. Soehadi Prijonegoro Hospital in Sragen from August to September 2022 by consecutive sampling. The control group (n=15) received standard therapy, and the treatment group (n=15) received standard therapy plus Omega-3 at a dose of 1600 mg/day. IL-6 and MDA levels were measured when the subject was admitted to the hospital and there was clinical improvement.Results: There was a significant difference in reduced IL-6 levels (P=0.001), decreased MDA levels (P=0.001), and the duration of clinical improvement (P=0.042) between the treatment group and the control group. There was a moderate correlation between the decrease in IL-6 (R=0.480) and MDA (R=0.459), while the duration of clinical improvement had a strong correlation (R=0.756) in the treatment group.Conclusion: Supplementation of Omega-3 was effective in reducing IL-6, MDA levels, and the duration of clinical improvement in community-acquired pneumonia patients.